Containing the Transmission of COVID-19: A Modeling Study in 160 Countries - Niu, Yan; Rui, Jia; Wang, Qiupeng; Zhang, Wei; Chen, Zhiwei; Xie, Fang; Zhao, Zeyu; Lin, Shengnan; Zhu, Yuanzhao; Wang, Yao; Xu, Jingwen; Liu, Xingchun; et al. (Frontiers in Medicine, 2021)
Background: It is much valuable to evaluate the comparative effectiveness of the coronavirus disease 2019 (COVID-19) prevention and control in the non-pharmacological intervention phase of the pandemic across countries and identify useful experiences that could be generalized worldwide. Methods: In this study, we developed a susceptible – exposure – infectious – asymptomatic – removed (SEIAR) model to fit the daily reported COVID-19 cases in 160 countries. The time-varying reproduction number (Rt) that was estimated through fitting the mathematical model was adopted to quantify the transmissibility. We defined a synthetic index (IAC) based on the value of Rt to reflect the national capability to control COVID-19 was finally calculated by. Results: The goodness-of-fit tests showed that the SEIAR model fitted the data of the 160 countries well. At the beginning of the epidemic, the values of Rt of countries in the European region were generally higher than those in other regions. Among the 160 countries included in the study, all European countries had the ability to control the COVID-19 epidemic. The Western Pacific region did best in the managing of continuous control of the epidemic, with a total of 73.76% of countries can continuously controlled the COVID-19 epidemic, while only 43.63% of the countries in the European region continuously controlled the epidemic, followed by, the Region of Americas with 52.53% of countries, South-east Asia Region with 48% of countries, African region with 46.81% of countries, and Eastern Mediterranean Region with 40.48% of countries. Conclusion: Large variations in controlling the COVID-19 epidemic existed across countries. The world could benefit the experience of some countries that demonstrated the highest containment capabilities.